(untitled) (Cultura Económica, 2019)
The present article analyzes, from the Peruvian experience, the viability of the state contribution to the expansion and the strengthening of the solidarity economic modalities, and, consequently, to its predominance in the whole of the economic order. For this purpose, the evolution of the national regulations referred to this type of organizations is focused, and its correlation with the creation of favorable conditions for their growth and consolidation. It is determined that, in Peru, the state action has been marked by the development model and the economic interests advocated by the political class in the government, so that, eventually, it has contributed to the emergence and expansion of the associative economic modalities, as well as its desactivation. It is also argued that the restitution of associative economic modalities in the state public agenda, and the validity of differentiated measures in their treatment, from the recognition of their social purpose, have depended on the organizational level and the capacity of intermediation and defense of interests achieved by their representative actors.